An ICT Tool for Visualising and Archiving Measurement Data Collected using Mobile Sensors - Andrzej GRABOWSKI (Narzędzie teleinformatyczne do wizualizacji i archiwizacji danych pomiarowych zbieranych za pomocą przemieszczających się sensorów, 2019)
Many sectors require the use of dedicated ICT systems to collect data from dispersed and oftentimes moving measurement systems. This is associated with the increasingly-common use of unmanned vehicles, mostly flying ones, carrying various measurement systems, such as concentration sensors detecting selected gases. The measurement data can be transmitted wirelessly to a central server. The article presents the architecture of a universal ICT tool that, owing to its flexible application programming interface, can be used for integrating, archiving and visualising data coming from a heterogeneous network of measurement devices in real time.
Keywords: Wizualizacja i archiwizacja danych pomiarowych